Carrot (Daucus carota) Production in the Sandy Soils of North Florida: Nitrogen Fertilization Guidelines - Morgan Morrow; Vivek Sharma; Robert Hochmuth; Charles Barrett; Marina Burani-Arouca (EDIS)
This publication discusses carrot growth characteristics and provides nitrogen fertilizer best management practices for carrot crops growing in north Florida. The nitrogen management guidelines presented in this publication are based on multiyear field-based research conducted by UF/IFAS. Written by Morgan Morrow, Vivek Sharma, Robert C. Hochmuth, Charles Barrett, and Marina Burani-Arouca, and published by the UF/IFAS Department of Agricultural and Biological Engineering, July 2023.